Somatosensory Amplification Scale—Chinese version: psychometric properties and its mediating role in the relationship between alexithymia and somatization - Tan, Yafei; An, Xiaoran; Cao, Menglu; Van den Bergh, Omer (Frontiers in Psychology, 2024)
The Somatosensory Amplification Scale (SSAS) was designed to measure individual’s tendency to experience visceral and somatic sensations as unusually intense, disturbing and alarming. In this study, we aimed to investigate the reliability and validity of the SSAS in the Chinese general population, as well as the mediating effect of somatosensory amplification in the relationship between alexithymia and somatization. A total of 386 healthy adults were enrolled in this study. Participants completed the Chinese versions of the Somatosensory Amplification Scale (SSAS-C), the somatization subscale of the Symptom Check List 90 (SCL-90 som), the Toronto Alexithymia Scale (TAS-20), and the Short form Health Anxiety Inventory (SHAI). One hundred and thirty-three participants were randomly selected to complete the SSAS-C again two weeks after the initial assessment. The reliability and validity of the SSAS-C were analyzed. Confirmatory factor analysis showed that the one-factor model achieved adequate model fits; one item was deleted due to low factor loading. The revised SSAS-C showed good internal consistency and test-retest reliability. The SSAS-C scores correlated positively with the scores of SCL-90 som, TAS-20 and the SHAI, showing good convergent validity. In addition, somatosensory amplification mediated the association between alexithymia and somatization. The Chinese version of SSAS has acceptable reliability and validity for the general population. In addition, alexithymia may increase somatization through higher somatosensory amplification.